Effect of irrigation protocols on chemical smear layer formation over the post-space dentin - Gelio, Mariana Bena [UNESP]; Ramos, Anna Thereza Peroba Rezende [UNESP]; Zaniboni, Joissi Ferrari [UNESP]; Escalante-Otárola, Wilfredo Gustavo; Besegato, João Felipe [UNESP]; Kuga, Milton Carlos [UNESP] (Wiley, 2022)
This study evaluated the effect of irrigation protocols using 95% ethanol (ET) or 1% peracetic acid (PA) prior the use of 2% chlorhexidine (CHX) compared to distilled water (DW) on the chemical smear layer (CSL) formation and incidence of open dentin tubules at the apical, medium, and cervical third of the post-space dentin. Scanning electron microscopy (SEM) and electron dispersive spectroscopy (EDS) images were used. Forty bovine roots were endodontically treated. After, post-space preparation was performed and the roots were randomized in four groups (n = 10) according to the irrigation protocol: DW, CHX, CHX-ET and CHX-PA. The chemical composition of CSL and the incidence of open dentin tubules at the post-space thirds were evaluated by EDS (500× magnification) and SEM (2000× magnification) images, respectively. Data from chemical composition of CSL were descriptively analyzed, while the incidence of open dentin tubules was evaluated by scores and submitted to Kruskal-Wallis and Dunn test (p =.05). Cl, Bi, and Si were the chemical elements most found over the dentin after the irrigation with CHX and CHX-ET. Moreover, CHX and CHX-ET showed the highest incidence of CSL (p <.05), but without difference between them (p >.05), regardless of the post-space third. DW and CHX-PA showed similar incidence of CSL (p >.05). No difference on the incidence of open dentin tubules was found for any irrigation protocol and post-space third (p >.05). The use of 1% PA prior the post-space irrigation with CHX decrease the incidence of CSL. Research Highlights: The post-space irrigation with chlorhexidine results in the formation of chemical smear layer. Ethanol is not capable to remove the chemical smear layer. Peracetic acid is more effective to remove the chemical smear layer.
Keywords: chlorhexidine; fiber post; peracetic acid; scanning electron microscopy